2020
DOI: 10.48550/arxiv.2010.00597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Electro-Weak Phase Transition at Colliders: Confronting Theoretical Uncertainties and Complementary Channels

Andreas Papaefstathiou,
Graham White

Abstract: We explore and contrast the capabilities of future colliders to probe the nature of the electro-weak phase transition. We focus on the real singlet scalar field extension of the Standard Model, representing the most minimal, yet most elusive, framework that can enable a strong first-order electro-weak phase transition. By taking into account the theoretical uncertainties and employing the powerful complementarity between gauge and Higgs boson pair channels in the searches for new scalar particles, we find that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(30 citation statements)
references
References 93 publications
(142 reference statements)
0
30
0
Order By: Relevance
“…We will study the theory near its Z 2 symmetric limit, see the discussion in Section IV below, taking | sin θ| < 0.1 and assuming the new excitation to be heavier than the SM Higgs. The remaining parameter space is then relatively unconstrained by current experiments [13,18,21,32]. We will not consider experimental constraints further in this paper as our focus is on the finite-T behavior of the theory.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We will study the theory near its Z 2 symmetric limit, see the discussion in Section IV below, taking | sin θ| < 0.1 and assuming the new excitation to be heavier than the SM Higgs. The remaining parameter space is then relatively unconstrained by current experiments [13,18,21,32]. We will not consider experimental constraints further in this paper as our focus is on the finite-T behavior of the theory.…”
Section: Modelmentioning
confidence: 99%
“…We work in the real-singlet extension of the Standard Model which we shall refer to as xSM, following [9]. Several one-loop analyses of the EWPT exist in this minimalistic yet realistic BSM model, see [9][10][11][12][13][14][15][16][17][18][19][20][21] and references therein, but we are not aware of existing two-loop calculations in the finite-T context. Two-loop studies in other scalar extensions and in the MSSM have reported on considerable deviations from the one-loop behavior [22][23][24][25][26][27], motivating a detailed two-loop investigation of the xSM as well.…”
Section: Introductionmentioning
confidence: 99%
“…in [84][85][86]. It will be interesting to perform such an analysis within the model in question to study complementarity between collider and gravitational wave experiments [87][88][89]. We leave study of these and similar processes for future.…”
Section: Relation To Parameters Of Supersymmetric Modelmentioning
confidence: 99%
“…Determining the true nature of EWSB therefore requires ruling out or discovering any such new states. In the context of the minimal, but challenging to detect, real singlet extension to the SM as a test case, it has been demonstrated that a proton-proton collider with a centre-of-mass energy of 100 TeV [1,[46][47][48][49][50][51], or perhaps even 27 TeV [51], can exclude or discover the presence of a singlet field, provided it couples to the SM sufficiently strongly to induce a SFO-EWPT. This statement has been shown to remain true even when taking a liberal approach to the theoretical uncertainties involved [51].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the minimal, but challenging to detect, real singlet extension to the SM as a test case, it has been demonstrated that a proton-proton collider with a centre-of-mass energy of 100 TeV [1,[46][47][48][49][50][51], or perhaps even 27 TeV [51], can exclude or discover the presence of a singlet field, provided it couples to the SM sufficiently strongly to induce a SFO-EWPT. This statement has been shown to remain true even when taking a liberal approach to the theoretical uncertainties involved [51]. A potentially complementary approach towards discovery [49,50,[52][53][54] is to observe a gravitational wave background which would be present if the transition were strong enough.…”
Section: Introductionmentioning
confidence: 99%